Hypnotherapy Technique to Reduce Anxiety Levels in Elderly with Hypertension - Marisca Agustina (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2024)
Background: One of the non-pharmacological intervention that can be used is hypnotherapy. This intervention uses suggestions that will relax the client's condition so that the brain produces the hormones serotonin, endorpine, and activation of autonomic nerve responses. At the same time the neuroendocrine system will also lower levels of cortisol, glucocorticoids, gonadocorticoids, epinephrine, norepinephrine and will act directly on the alpha androgenic receptors of vascular smooth muscle, thus causing vasodilation of blood vessels, lowering total peripheral pressure and decreasing blood pressure, pulse, and breathing. Objectives: This study is to determine the effect of hypnotherapy techniques on reducing anxiety levels in elderly families with hypertension at RT 10/RW 05 Lenteng Agung, South Jakarta. Methods: This study employed a quantitative pre-experimental design with a one-group pre-test post-test approach to examine the effect of an intervention on anxiety levels in elderly individuals with hypertension. The study population consisted of 39 elderly individuals, with 15 participants meeting the inclusion criteria. Data were collected in 2023, and the sample was selected using total sampling, consisting of 9 women and 6 men. Participants were observed before and after the intervention to assess changes in anxiety levels. Results: This study showed that after being given hypnotherapy technique treatment, the majority experienced a decrease in anxiety levels, namely mild anxiety as many as 11 elderly (73.3%) and respondents who experienced moderate anxiety as many as 4 elderly (46.7%) Conclusion: The majority of elderly individuals with hypertension experienced severe anxiety before receiving hypnosis techniques. After the application of hypnosis, most experienced a reduction in anxiety to mild levels. This demonstrates that hypnosis techniques have a significant effect in reducing anxiety levels in elderly individuals with hypertension